AIDS as God’s Punishment: Examining Ibn Majah’s Sexual Ethics And Implication of Transgression - Maufur Maufur; Saifuddin Zuhri (ESENSIA: Jurnal Ilmu-Ilmu Ushuluddin, 2019)
There are still many religious communities who regard AIDS as a curse and punishment from God. Where do the assumptions and discourse come from? And what are the consequences of these assumptions. This paper then sees that one of these assumptions resulted from the Sunan Ibn Majah (number 4019) where there is the word Fahisha. But in the end of our article, we conclude that the Hadith in Ibn Majah is far from talking about divine punishment, rather about the Tawhid according to which Muslims should behave in this world. The Tawhid serves as Islamic morality that is extended from the individual to the social. The Hadith as a whole is basically dealing with social problems as a result of social ignorance to the principles of the Tawhid, which consist of liberation of human consciousness, human equality and social solidarity as the basis of Islamic morality.